Perbandingan Kebijakan Hukum Pidana Terhadap Anak Pada Hukum Peninggalan Belanda (Wetboek Van Straftrecht) dengan KUHP Nasional - Tuba, La; Arisaputra, Arisaputra (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2026)
Children are future leaders who can shape Indonesia into a more advanced nation in terms of politics, socio-culture, economy, law, and technology. The term "child in conflict with the law" refers to a child in conflict with the law who is 12 (twelve) years old but not yet 18 (eighteen) years old who is suspected of committing a crime. The Dutch Law (Wetboek van Straftrecht) that was in use was a legal product of Dutch heritage. However, with the development of Indonesian society, a new National KUHP (Kitab Undang-Undang Hukum Pidana/Criminal Code) was finally formed which was promulgated on January 1, 2023. This study aimed to determine the criminal law policies for children in conflict with the law in the National KUHP and compare the Wetboek van Straftrecht with the National KUHP concerning criminal law policies for children who were in conflict with the law. This was normative research conducted by examining secondary data or existing literature. The data collection method used was library research by collecting and studying library data from the legal materials used. The data analysis method used was descriptive qualitative. The criminal law policy for children in conflict with the law in the National KUHP regulated the minimum and maximum age limits for children in conflict with the law, diversion, actions, and types of punishment that could be imposed. Meanwhile, the Wetboek van Straftrecht did not regulate the minimum age limit for children in conflict with the law. The actions that could be imposed were limited to returning to parents/guardians and handing over to the government which only applied to certain criminal acts, as well as a reduced penalty of 1/3 of adults' penalty. However, these lacks had been completed in the National KUHP by prioritizing the best interests of the children.